Clinical Prevalence of Peste Des Petits Ruminants (PPR) Disease in Small Ruminants at the Urban Areas of Hyderabad, Sindh - Asad Ali Khaskheli; M. Ibrahim Khaskheli; Allahjurio Khaskheli; Gulbhar Khaskheli; Rani Abro; Ghulam Shabir Barham (Journal of Basic & Applied Sciences, 2017)
Peste des Petits Ruminants is a highly contagious viral disease of small ruminants, caused by Peste des Petits Ruminants virus (PPRV), spreading worldwide in these days. Thus, current study was planned to check the prevalence percentage of PPR in small ruminants especially in goat and sheep surrounding the urban areas of Hyderabad district of Pakistan. A total of two hundred goat (n=200) were examined during study period. The highest prevalence percentage was observed for PPR (35%) followed by respiratory tract infection (17%), urine incontinence (10%), tympany (9.5%) and indigestion (6%). The prevalence percentage of fracture (1.5%) was lowest among all followed by retained placenta (2%), dystokia (2.5%), mastitis (3%) and abortion (3.5%). Whereas, wound (4.5%) and enterotoxaemia (5.5%) showed moderate prevalence. Similarly, a total two hundred sheep (n=200) were examined and prevalence of different disorders in sheep was found quietly different from the goat. The PPR appeared to be most prevalent problem (30%) in sheep too followed by indigestion (15.5%), respiratory tract infection (13.5%), tympany (12.5%) and wound (7.5%). Fracture appeared as least prevalent problem (1%) followed by dystokia (1.5%), retained placenta (3%), mastitis (3.5%) and abortion (5%). The moderate prevalence was of enterotoxaemia (7%); where, as prevalence of urine incontinence was recorded zero (0%). Overall Prevalence percentages of different disorders in both species indicate that PPR (32.5%) appeared as most prevalent disease followed by respiratory tract infections (15.25%), tympany (11%), indigestion (10.75%) and enterotoxaemia (6.25%). Furthermore; fracture appeared as least prevalent complaint (1.25%) followed by dystokia (2%), retained placenta (2.5%), mastitis (3.25%) and dystokia (4.25%). As for as urine incontinence (5%) and enterotxaemia (6.25%) are concerned, their prevalence was found moderate. No doubt PPR is one of the major emerging issue for small ruminant production therefore current study was planned to provide a proper baseline information so that infected heads could be identified on very early stage for their timely cure and prevention.